Implementasi nilai-nilai Etika, Moral dan Akhlak dalam perilaku belajar di STIT Raden Wijaya Mojokerto - Aan Eko Khusni Ubaidillah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
The problems we face today live in a time of moral degradation and destruction. People feel proud if they can imitate the trend carried by the West; both in thought and lifestyle. Ironically, not a few generations of Muslims who terpedaya with the trend. They make Western values as their standard of behavior and morals. Meanwhile, Islamic morality is increasingly felt strange and difficult to practice in the midst of society facing such problems plural and complex. The purpose of this study are: 1) To describe the steps Implementation of values of Ethics, Moral and Morals in learning behavior in STIT Raden Wijaya Mojokerto. 2) To describe the supporting and inhibiting factors Implementation of Ethics, Morals and Morals values in the behavior of learning in STIT Raden Wijaya Mojokerto This research type is field research research using qualitative approach. Data collection techniques include observation, interview, and documentation. Data analysis technique uses descriptive explorative, that is by describing state and phenomenon status. Based on the exposure of the analysis of data sources can be concluded that: 1) Steps Implementation of values of Ethics, Morals and Morals in the behavior of learning in STIT Raden Wijaya Mojokerto is the first institution to make a mature planning, then applied with the pattern pembiasaan. 2) To describe the supporting and inhibiting factors Implementation of Ethics, Morals and Morals values in learning behavior in STIT Raden Wijaya Mojokerto consists of internal factors (consisting of heredity, gender, physical character, personality, intelligence and talent) and external ( consisting of education, religion, culture, environment and socio-economic)